IN-HOSPITAL MORTALITY RATE AND TRENDS IN DOOR-TO-BALLOON TIME IN PRIMARY PERCUTANEOUS CORONARY INTERVENTION IN PATIENTS WITH ACUTE ST ELEVATION MYOCARDIAL INFARCTION IN AFIC-NIHD RAWALPINDI - Rehman, Waheed Ur; Khan, Muhammad Qaiser; Aziz, Sohail; Siddiqa, Aysha; Ghani, Imran; Shabbir, Muhammad; Khan, Qurban (Pakistan Armed Forces Medical Journal, 2015)
Objective: To determine in-hospital mortality rate and trends in Door-to-Balloon Time in Primary percutaneous coronary intervention (Primary-PCI) in patients with acute ST elevation Myocardial Infarction (AMI). Study Design: Descriptive cross sectional study. Place and Duration of Study: This study was conducted at AFIC/NIHD Rawalpindi from Oct 2011 to Jan 2015. Material and Methods: Total of 1256 patients with acute ST elevation Myocardial Infarction (AMI) from Oct 2011 to Jan 2015 who underwent primary PCI were included in this study. We determined the in-hospital mortality and yearly trend in door to balloon time (DTBT). Procedural success was defined as restoration of TIMI-III flow in the Infarct Related Artery (IRA) or culprit artery with less than 30% residual stenosis and discharge from hospital. Results: Overall in-hospital mortality was 3.82% (48) including 1.12% (14) procedural mortality. Most of the patients’ fall into the category of < 60 minutes. Patients with longer door-to-balloon time > 90 minutes had higher mortality amongst the door-to-balloon time groups (< 60 minutes = 4.8%, 60-89 minutes = 2.85%, 90-120 minutes = 15.27% p < 0.001). Conclusion: Door-to-balloon time is associated with mortality in patients undergoing primary percutaneous coronary intervention for ST elevation myocardial infarction. Time to treatment should be as short as possible, even in centers currently providing primary percutaneous coronary intervention within 90 minutes. Further studies are needed to take into account total ischemic time and pre-hospital delays.